АРДЧИЛЛЫН ХӨГЖИЛД УЛС ТӨРИЙН НАМЫН ГҮЙЦЭТГЭХ ҮҮРЭГ - Б.Баярбаатар; Д. Бумдарь (Politology, 2023)
In 1990, Mongolia made a reasonably peaceful transition from a one-party to a multi- party democratic political system. The unavoidable transition to democracy signaled the start of the growth of a political party system that would find a unique opportunity to evolve into a top-tier system of government. The groundwork was thus set for political parties to take part in governmental functions legally. Within the framework of this article, we aim to express the close connection between political parties and democracy at the empirical level. After that, we wrote about how the growth of democracy was closely related to the type, role, and system of political parties. Because a political party remains at the center of every democracy.